2016
DOI: 10.1111/1365-2664.12759
|View full text |Cite
|
Sign up to set email alerts
|

A fresh approach reveals how dispersal shapes metacommunity structure in a human‐altered landscape

Abstract: 1.To understand species losses from disturbed landscapes, it is important to distinguish the effects of degraded environmental conditions from those caused by barriers to dispersal between habitat patches. To assess the relative importance of these effects, we developed a new approach using permutation and association tests applied to rank abundance data, using the invertebrate fauna of two rivers in two seasons. 2. Our study streams were Hughes Creek and Seven Creeks, in south-eastern Australia, which have bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 28 publications
(45 reference statements)
2
42
0
Order By: Relevance
“…Other studies also found that freshwater communities may be only weakly dispersal limited, even up to a distance of 300 km (Cañedo-Argüelles & Rieradevall, 2011;Viana et al 2015, but see Heino et al, 2015;Downes, Lancaster, Glaister, & Bovill, 2017). Other studies also found that freshwater communities may be only weakly dispersal limited, even up to a distance of 300 km (Cañedo-Argüelles & Rieradevall, 2011;Viana et al 2015, but see Heino et al, 2015;Downes, Lancaster, Glaister, & Bovill, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies also found that freshwater communities may be only weakly dispersal limited, even up to a distance of 300 km (Cañedo-Argüelles & Rieradevall, 2011;Viana et al 2015, but see Heino et al, 2015;Downes, Lancaster, Glaister, & Bovill, 2017). Other studies also found that freshwater communities may be only weakly dispersal limited, even up to a distance of 300 km (Cañedo-Argüelles & Rieradevall, 2011;Viana et al 2015, but see Heino et al, 2015;Downes, Lancaster, Glaister, & Bovill, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Unsuccessful colonisation may be due to environmental constraints. For example, water temperatures at downstream locations exceed 29°C when the air temperature reaches ~34°C, which is a relatively common occurrence during summers (Downes et al., ). Water temperatures of 30°C are extreme for most insects (Lancaster & Downes, ) and can be associated with low oxygen concentrations in Hughes Creek as well (Lancaster, Downes, & Glaister, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sandy locations thus have sparsely treed riparian zones, low densities of detritus, a bed of shifting sand and shallow, warm water. Temperature loggers showed that water temperatures at downstream locations were often > 29°C and reached up to 36°C on hot days, for example where air temperature exceeded 40°C (Downes et al., ). Downstream locations have approximately half the number of invertebrate species found in cooler, more intact upstream areas (Downes et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations